1994
DOI: 10.1016/0014-5793(94)01001-3
|View full text |Cite
|
Sign up to set email alerts
|

Single channel activity of the ryanodine receptor calcium release channel is modulated by FK‐506

Abstract: The immunosuppressant drug increased the open probability of ryanodine receptor calcium release channels, formed by incorporation of terminal cisternae vesicles from rabbit skeletal muscle into lipid bilayers, with cis (cytoplasmic) calcium concentrations between 10 -7 M and 10 -3 M. FK-506 increased mean current and channel open time and induced long sojourns at subconductance levels that were between 28% and 38% of the maximum conductance and were distinct from the ryanodine-induced subconductance level at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 31 publications
9
94
0
Order By: Relevance
“…Interestingly, there is a Val-Pro-Leu-Val motif (amino acids 4594 -4597 for human RyR2) within putative transmembrane segment M6 (nomenclature of the 10TM model (56)), which could constitute part of the FKBP-binding core. Notably, the specific residue Pro-4595 was initially proposed to be involved in FKBP binding, based on the fact that FKBP has a peptidyl-prolyl cis-trans isomerizing activity and that its dissociation destabilizes the channel and results in appearance of sub-conductance states (14,23,24). Consistent with this, it has also been suggested that proline residues contained within ␣-helical transmembrane segments are involved in conformational changes within transmembrane domains of ion channels, transport proteins and G-protein-coupled receptors (57,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there is a Val-Pro-Leu-Val motif (amino acids 4594 -4597 for human RyR2) within putative transmembrane segment M6 (nomenclature of the 10TM model (56)), which could constitute part of the FKBP-binding core. Notably, the specific residue Pro-4595 was initially proposed to be involved in FKBP binding, based on the fact that FKBP has a peptidyl-prolyl cis-trans isomerizing activity and that its dissociation destabilizes the channel and results in appearance of sub-conductance states (14,23,24). Consistent with this, it has also been suggested that proline residues contained within ␣-helical transmembrane segments are involved in conformational changes within transmembrane domains of ion channels, transport proteins and G-protein-coupled receptors (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Given the profound effects of FKBP on both the channel activity and conductance of the RyR and its peptidyl-prolyl cis-trans isomerizing activity, it was suggested that FKBP binds to Pro-4595 (numbering given for the human RyR2), a residue located within a hydrophobic, predicted transmembrane domain at the RyR C terminus (14,23,24). Furthermore, it was proposed that the FKBP-binding site may reside in, or near, the conduction pore of the channel, because FKBP12 binding to RyR1 was found to be voltage-dependent in single channel electrophysiological experiments (25).…”
mentioning
confidence: 99%
“…Under physiological conditions (i.e., the absence of immunosuppressive drugs), FKBPs are though to bind to RyRs with high affinity and stabilize the closed state of the channel (Ahern et al 1994;Brillantes et al 1994;McCall et al 1996;Ahern et al 1997;Marx et al 1998;Marx et al 2001). Removal of FKBP12, by preventing rebinding with an immunosuppressive drug or as the result of a genetic FKBP deficiency leads to greater open probability of the channel and longer mean open times (Ahern et al 1997;Marx et al 1998;Shou et al 1998).…”
Section: Calsequestrinmentioning
confidence: 99%
“…Skeletal SR was isolated from the back and leg muscles of New Zealand White rabbits, and heavy SR was collected from the 35-45% (w v À1 ) interface of a discontinuous sucrose gradient, centrifuged and resuspended (Ahern et al, 1994). Cardiac SR was prepared from sheep heart (Chamberlain & Fleischer, 1988;Laver et al, 1995).…”
Section: Isolation Of Sr Vesiclesmentioning
confidence: 99%